MOTIVATION AND TECHNOLOGY EXPOSURE AS DETERMINANTS OF HIGH SCHOOL STUDENTS’ INTEREST IN AGRICULTURE: EVIDENCE FROM INDONESIA - Rachmi Satwhikawara; Khairun Nisa Il Fiqriyah (Penelitian dan Pengembangan Ilmu, 2025)
The declining interest of young generations in agriculture has become a serious challenge to the sustainability of the agricultural sector, particularly in developing countries. This study aims to analyze the influence of motivation and technology exposure on high school students’ interest in agriculture. A quantitative research approach was employed using primary data collected through a structured questionnaire administered to 101 senior high school students in Bekasi Regency, Indonesia. The data were analyzed using multiple linear regression, supported by validity, reliability, and classical assumption tests. The results indicate that motivation has a positive and significant effect on students’ interest in agriculture, while technology exposure also shows a significant influence, although to a lesser extent. Simultaneously, motivation and technology exposure significantly affect students’ agricultural interest. These findings suggest that psychological factors and technological familiarity play an important role in shaping youth perceptions and interest toward agricultural careers. This study contributes empirical evidence on youth engagement in agriculture from an emerging agricultural region and highlights the importance of integrating motivational strategies and technology-based learning into agricultural education. The findings provide practical implications for educators, policymakers, and educational institutions in designing programs aimed at attracting younger generations to the agricultural sector.